Development of an adjustable-motorized wheelbarrow / Muhammad Syahrin Suhaimi - Suhaimi, Muhammad Syahrin (2022)
The evolution of wheelbarrow is evolving rapidly than a few centuries before. However, the evolution is not too drastic nowadays because of the demand in high tech wheelbarrow is not as high as the demand in other technology but there are still some companies take this opportunity to create a wheelbarrow supported with modern technology like motor, engine and so on. However, not everyone can afford to buy the wheelbarrow because of its high price. So, to increase the total users for high tech wheelbarrow, the final year project has been done. Final Year Project (FYP1) is an adjustment and improvement of the product that already exist. The concept design and fabrication have to be done. The final product should be able to work functionally to show that this FYP project is a success